INOVASI KEBIJAKAN PEMERINTAH DAERAH NOMOR 18 TAHUN 2008 TENTANG PENGELOLAAN SAMPAH ZERO WASTE (Studi Kasus Di Kelurahan Menala Kecamatan Taliwang Kabupaten Sumbawa Barat Tahun 2024) - Angga Muhfi Azhar,; Lalu Sopan Tirta Kusuma,; Zulhadi, Zulhadi; Inka Nusamuda Pratama, (Journal of Innovation Research and Knowledge, 2025)
This study examines the implementation of local government policies on the zero waste program in Menala Village, West Sumbawa Regency, based on Regional Regulation Number 18 of 2008 concerning Waste Management. This study aims to analyze the effectiveness of the zero waste program in overcoming waste problems while identifying supporting and inhibiting factors in its implementation. The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with relevant stakeholders including the village government, environmental services, and the community, complemented by policy document analysis and field observations. This study uses a qualitative method with a descriptive approach, collecting data through interviews, observations, and documentation studies. The results of the study indicate that the implementation of the zero waste program in Menala Village has produced several significant achievements. First, the formation of an integrated waste management system that includes a waste bank at the RW level and TPS 3R as a waste processing center. Second, increased community participation in sorting household waste after intensive socialization. Third, the development of a creative economy based on waste recycling involving community groups. However, this program still faces various obstacles such as low awareness of some residents in sorting waste, limited operational budget, and resistance to behavioral changes in waste management. In conclusion, this policy has great potential in creating a cleaner and more sustainable environment, but requires strengthening in terms of socialization, improving facilities, and more comprehensive regulatory support so that it can be implemented more effectively and comprehensively